Desain E-Modul menggunakan Pendekatan Open Ended Berbasis Etnomatematika Tari Gambyong Materi SPLDV - Kamilah, Hana; Mawarsari, Venissa Dian; Prihaswati, Martyana (Mandalika Mathematics and Educations Journal, 2024)
The mathematics teaching materials used by teachers today are still printed teaching materials provided by the government. As a result, it is ineffective to improve students' learning outcomes because they seem discouraged and bored while learning. Thus, it is important to design teaching materials that utilize technological developments so that they are easily accessible to students to learn mathematics anytime and anywhere. This study aims to design a valid E-Module with an Open Ended approach based on Gambyong Dance Ethnomathematics on grade VIII SPLDV material. This research uses the Research and Development (R&D) research methodology with the ADDIE development model which is limited to the analysis, design and development stages. The data analysis techniques used include needs analysis, media expert validation analysis and material experts. This study produced an E-Module design along with the results of E-Module validation from media experts with an average assessment of 3.5 which is classified as a valid category and material experts with an average assessment of 3.6 which is classified as a valid category. The average combined E-Module assessment from media experts and material experts obtained a score of 3.54 in the valid category. This shows that the E-Module design is feasible to be tested on students during math learning.